The estuarine geochemical reactivity of Zn isotopes and its relevance for the biomonitoring of anthropogenic Zn and Cd contaminations from metallurgical activities: Example of the Gironde fluvial-estuarine system, France. (1st December 2015) - Petit, Jérôme C.J.; Schäfer, Jörg; Coynel, Alexandra; Blanc, Gérard; Chiffoleau, Jean-François; Auger, Dominique; Bossy, Cécile; Derriennic, Hervé; Mikolaczyk, Mathilde; Dutruch, Lionel; Mattielli, Nadine
Abstract: Zinc stable isotopes measurements by MC-ICP-MS, validated by laboratory intercalibrations, were performed on wild oysters, suspended particles and filtered river/estuarine water samples to provide new constraints for the use of Zn isotopes as environmental tracers. The samples selected were representative of the long range (400 km) transport of metal (Zn, Cd, etc.) contamination from former Zn-refining activities at Decazeville (i.e. δ 66 Zn > 1‰) and its phasing out, recorded during 30 years in wild oysters from the Gironde Estuary mouth (RNO/ROCCH sample bank). The study also addresses additional anthropogenic sources (urban and viticulture) and focuses on geochemical reactivity of Zn in the turbidity gradient and the maximum turbidity zone (MTZ) of the fluvial Gironde Estuary. In this area, dissolved Zn showed a strong removal onto suspended particulate matter (SPM) and progressive enrichment in heavy isotopes with increasing SPM concentrations varying from δ 66 Zn = −0.02‰ at 2 mg/L to +0.90‰ at 1310 mg/L. These signatures were attributed to kinetically driven adsorption due to strongly increasing sorption sites in the turbidity gradient and MTZ of the estuary. Oysters from the estuary mouth, contaminated sediments from the Lot River and SPM entering the estuary showed parallel historical evolutions (1979–2010) for Zn/Cd ratios but not for δ 66 Zn values. Oysters had signatures varying from δ 66 Zn = 1.43‰ in 1983 to 1.18‰ in 2010 and were offset by δ 66 Zn = 0.6–0.7‰ compared to past (1988) and present SPM from the salinity gradient. Isotopic signatures in river-borne particles entering the Gironde Estuary under contrasting freshwater discharge regimes during 2003–2011 showed similar values (δ 66 Zn ≈ 0.35 ± 0.03‰; 1SD, n = 15), i.e. they were neither related to former metal refining activities at least for the past decade nor clearly affected by other anthropogenic sources. Therefore, the Zn isotopic signatures in Gironde oysters reflect the geochemical reactivity of Zn in the estuary rather than signatures of past metallurgical contaminations in the watershed as recorded in contaminated river sediments. The study also shows that the isotopic composition of Zn is strongly fractionated by its geochemical reactivity in the Gironde Estuary, representative of meso–macrotidal estuarine systems.